Experimental Study on Anisotropic Strength and Deformation Behavior of a Coal Measure Shale under Room Dried and Water Saturated Conditions - Jingyi Cheng; Zhijun Wan; Yidong Zhang; Wenfeng Li; Syd S. Peng; Peng Zhang (Shock and Vibration)
This paper presents an experimental investigation of anisotropic strength and deformation behavior of coal measure shale. The effect of two factors (i.e., anisotropy and water content) on shale strength and deformation behavior was studied. A series of uniaxial and triaxial compression tests were conducted on both room dried and water saturated samples for different lamination angles. The test results indicate that (1) the compressive strength, cohesion, internal friction angle, tangent Young’s modulus, and axial strain corresponding to the peak and residual strengths of room dried specimens exhibit anisotropic behavior that strongly depends on the orientation angle (β); (2) in comparison to the room dried samples, the compressive strength and Young’s modulus as well as the anisotropy are all reduced for water saturated specimens; and (3) the failure mechanism of the samples can be summarized into two categories: sliding along lamination and shearing of rock material, with the type occurring in a particular situation depending strongly on the lamination orientation angles with respect to the major principal stress. According to the findings, it is strongly recommended that the effect of anisotropy and water content on the strength and deformation behavior of the rock must be considered in ground control designs.